Teste de figuras para discriminação fonêmica: proposta e aplicação - Carvalho, Beatriz dos Santos (2007)
Phonemic discrimination is the ability to differentiate the sounds of speech. The aim of this paper is to propose a picture test to evaluate the phonemic perception in children from 4 to 8 years old through minimum pairs. These were chosen based on phoneme opposition in relation to the binary value of each distinctive feature and on possible combinations among Place features ([labial]), [coronal], [dorsal]), and on syllabic structure oppositions. The test had to appreciate all Brazilian Portuguese phonemes, the words had to belong to child s vocabulary from 4 to 8 years old and they had also to be easily represented by pictures. In addition, the test had to be easily applied and it had to contribute to the diagnostic of the phonologic alterations and to scientific research on this field. Based on bibliographic references which approaches speech perception, phoneme discrimination, and existing tests to evaluate this or other language abilities, this paper proposed the Phoneme Discrimination Picture Test. The PDPT evaluates phonemic discrimination ability and it is composed of 30 minimum pairs (60 words) properly represented by pictures and arranged in flash cards. In order to explain the task to be performed there are four demonstration items. The 30 minimum pairs were arranged in 40 presentations in which 30 had 2 different words and 10 had 2 equal words. The tasks consisted of listening to 2 words (which could be different or equal) and pointing towards the flash card with the pictures that represented the words. A trial was carried out in order to apply the PDPT and check its quality, structure, arrangement, adequacy of the selected words and pictures. This trial was carried out in a private school in Santa Rosa, State of Rio Grande do Sul, Brazil. 49 subjects at ages 4:0 and 7:11 were evaluated, and from these, 24 studied at a private school and 25 at a public school. 22 subjects were female and 27 were male. All the subjects underwent a selection process in order to exclude any serious phonological alteration. At the conclusion of the trial it was possible to infer that the structure and arrangement of the PDPT were fit for the age group and for what it aimed to evaluate, and that it was easy and fast to apply, well-accepted by the children, and it did not required any special arrangement concerning testing environment and could also be very useful to diagnose phonologic alterations and to conduct scientific research in this field. However, the test needed to have two pictures altered. Analyzing the quantitative results, it was possible to check that there was no significant difference in performance among the 8 age groups, between both schools and sexes. Nevertheless, there was significant statistic difference in time spent to do the test in which the subjects from the public school spent more time. There is a hope that this test can be standardized so that one can have an estimate of the usual performance by the Brazilian population